Comparative analysis of fecal DNA extraction methods with phylogenetic microarray: Effective recovery of bacterial and archaeal DNA using mechanical cell lysis - Salonen, Anne; Nikkilä, Janne; Jalanka-Tuovinen, Jonna; Immonen, Outi; Rajilić-Stojanović, Mirjana; Kekkonen, Riina A.; Palva, Airi; de Vos, Willem M. (Journal of microbiological methods, 2010)
Several different protocols are used for fecal DNA extraction, which is an integral step in all phylogenetic and metagenomic approaches to characterize the highly diverse intestinal ecosystem. We compared four widely used methods, and found their DNA yields to vary up to 35-fold. Bacterial, archaeal and human DNA was quantified by real-time PCR, and a compositional analysis of different extracts was carried out using the Human Intestinal Tract Chip, a 16S rRNA gene-based phylogenetic microarray. The overall microbiota composition was highly similar between the methods in contrast to the profound differences between the subjects (Pearson correlations > 0.899 and 0.735, respectively). A detailed comparative analysis of mechanical and enzymatic methods showed that despite their overall similarity, the mechanical cell disruption by repeated bead beating showed the highest bacterial diversity and resulted in significantly improved DNA extraction efficiency of archaea and some bacteria, including Clostridium cluster IV. By applying the mechanical disruption method a high prevalence (67%) of methanogenic archaea was detected in healthy subjects ( n = 24), exceeding the typical values reported previously. The assessment of performance differences between different methodologies serves as a concrete step towards the comparison and reliable meta-analysis of the results obtained in different laboratories.